2012
DOI: 10.1039/c2jm35203f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reversible lithium intercalation in a new P′3-phase: Na2/3Mn1−yFeyO2 (y = 0, 1/3, 2/3)

Abstract: International audienceIn this contribution, new data on the reversible Li+ intercalation in iron substituted sodium manganates are provided. Novel Na2/3Mn1−yFeyO2 (y = 0, 1/3 and 2/3) compounds with a P′3-type structure are prepared from freeze-dried citrate precursors at 500 °C. A new structural element is the development of three-layer oxygen stacking contrary to the well-known P2-type Na2/3MnO2 with a two-layer sequence. The effect of Fe additives on the structure of Na2/3MnO2 was examined by XRD powder dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 45 publications
5
49
0
Order By: Relevance
“…In the case of transition metal ordering, we found that as expected it is mainly controlled by the difference in the ionic radii of M1 and M2, as illustrated by a large number of P2-layered oxides689121314151617181920212223242526272829303132333435. Large difference in ionic radii is favourable for forming ordered arrangement while small difference tends to form disordered arrangement.…”
supporting
confidence: 69%
“…In the case of transition metal ordering, we found that as expected it is mainly controlled by the difference in the ionic radii of M1 and M2, as illustrated by a large number of P2-layered oxides689121314151617181920212223242526272829303132333435. Large difference in ionic radii is favourable for forming ordered arrangement while small difference tends to form disordered arrangement.…”
supporting
confidence: 69%
“…Because the P2 and O3 phases have similar particle morphology (figure 5), the kinetic limitation related to the diffusion length is not responsible for the difference in performance. Research interest in the Na–Fe–Mn system as high-capacity electrode material is rapidly increasing, and now the electrode performance for P2- and O3-Na x [Fe y Mn 1 −  y ]O 2 with different chemical compositions has been determined [6870]. …”
Section: Layered Oxides As Na Insertion Host Materialsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among the various materials studied, sodium layered oxides (NaxMO2, M = transition metal) represent a promising family [8][9][10] . The most promising candidates are based on the Mn and / or Fe elements, which are the less expensive ones among the 3d elements: Nax(Mn,Fe)O2 [11][12][13][14][15][16][17][18][19] , Nax(Mn,Ni)O2 [20][21] , Nax(Mn,Mg)O2 [22][23][24] , Nax(Mn,Ni, Fe)O2 [25][26][27] , Nax(Mn,Co)O2 [28][29][30][31] Nax(Mn,Ni, Co)O2 [32][33][34][35][36][37][38][39] ,Nax(Li,Ni,Mn)O2 [39][40] .…”
Section: Introductionmentioning
confidence: 99%